Les effets du travail collectif entre enseignants et chercheurs : une étude de cas en anglais - Nolwenn Quéré (Recherches en Éducation)
The work we present is part of the e-FRAN IDEE (Digital Interactions for Education and Teaching) research project. Part of this study focuses on the effects of collective work between teachers and researchers during cooperative didactic engineering. Our research focuses on observing a collective conception of a digital resource in English. We use the theory of the documentational approach to didactics to uncover the impact of this work on the dynamics of individual and collective resource systems.